Hyper Mat! / Muhammad Asri Azuddin - Azuddin, Muhammad Asri (UiTM Perak Press, 2021)
In this digital era, most of the photograph are hard to be trusted. This is the digital pixels can be modified, rearrange and manipulate into something different from the original. The idea of manipulating visual are way back and one of the purposes and most used is in manipulating idea of creating a propaganda to provoke the audience. The idea of this provoking images and photograph is to spread the negative and hates. In the hand, photo manipulation also being used to cover the truth meaning within the image. The artist artwork takes advantage of those idea and use the digital photo manipulation as the main tools to deliver his idea literally to the viewers. The process of completing the artwork is arranged until the final outcome of the artwork. The satire element is implemented in the overall meaning of the artwork for society to digest. The artist feels like his responsible to educate the audience directly and indirectly through his artwork. Instead of many negative used related to digital manipulation, the tools itself can be use into a greater good for a better purpose. Some of the imaginative idea may be achieve using this digital pixel photograph so that the realistic outcome that the artist has imagine can be project vividly into the final product.